Penetapan Kadar Total Flavonoid dan Tanin Ekstrak Daun Bidara Arab (Ziziphus Spina-christi Lam) - Shinta Cania Maiza; Trie Yuni Elfasyari; Ghalib Syukrillah Syahputra (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2022)
Arabic Bidara Leaf (Ziziphus Spina-christi Lam) is one of the plants used as herbal medicine. Traditionally, the Arabic Bidara plant can be used as a medicine for wounds, eye diseases, and skin diseases. Previous research stated that the Bidara Arab plant contains secondary metabolites such as flavonoids, tannins, sterols, saponins and triterpenoids. This study aims to determine the total levels of flavonoids and tannins contained in the water extract of Bidara Arab leaves. The extraction method used in this research is the maceration method. In the study of determining the total flavonoid and tannin levels using UV-Vis Spectrophotometry, the wavelength used to determine the total flavonoid content was 441 nm and for the total tannin content was 740 nm. The standard used in this study was quercetin for total flavonoid content and gallic acid for total tannin content, made with several variations in concentration. The results showed that the total flavonoid content was 0.0869% and the total tannin content was 0.2864%..